Pengembangan Media Interaktif Sistem Pembumian Berbasis Articulate Storyline Untuk Meningkatkan Hasil Belajar Siswa - Nathanael Putra Sanyoto; Achmad Imam Agung; Fendi Achmad; Yulia Fransisca (CV. SINAR HOWUHOWU, 2026)
This research aims to Develop an interactive learning media assisted by Articulate Storyline on grounding system material to improve student learning outcomes. Electrical installation learning frequently relies on conventional methods lacking adequate visualization, resulting in suboptimal student comprehension. This research is a Research and Development (R&D) adapting the 4D Design (Define, Design, Develop, Disseminate). Data collection was conducted involving 10 students in the limited trial and 38 students in the limited dissemination stage, alongside lecturers and teachers as validators. The research instruments included expert validation sheets, user response questionnaires, affective and psychomotor observation guidelines, as well as pre-test and post-test items. The testing results proved this media is highly valid, achieving 84.00% from material experts and 84.89% from media experts. The practicality aspect reached the highly practical category through a limited dissemination score of 81.75% and a teacher response score of 86.22%. The effectiveness level recorded high criteria via an N-Gain score of 0.7285, supported by improvements in the affective domain (82.74%) and psychomotor domain (80.47%). In conclusion, this interactive media is highly feasible, practical, and effective to implement for improving comprehensive learning outcomes.